The Concurrent Validity and Responsiveness of the High‐Level Mobility Assessment Tool for Mobility Limitations in People With Multitrauma Orthopedic Injuries. Issue 3 (18th September 2013) - Williams, Gavin; Hill, Bridget; Kahn, Michelle
Abstract : Objective: To investigate the concurrent validity, responsiveness, and ceiling effect of the revised High‐Level Mobility Assessment Tool (HiMAT) in persons after orthopedic multitrauma. Design: Cross‐sectional sample of convenience. Setting: A large tertiary rehabilitation hospital. Participants: Forty‐three participants with orthopedic multitrauma lower limb injuries that resulted from motor vehicle accidents. Methods: This study compared the concurrent validity, responsiveness, and ceiling effects of the revised HiMAT, motor subsection of the Functional Independence Measure (FIM) instrument. Performances for all participants were concurrently scored on the motor FIM, revised HiMAT, and the Lower Extremity Functional Scale (LEFS) at initial testing, and 6 and 12 weeks after the decision to fully bear weight. Main Outcome Measurements: Revised HiMAT, motor FIM, and LEFS. Results: The correlation between the revised HiMAT and the motor FIM was moderate ( r = 0.49; P <.001) and partly induced by a ceiling effect in the motor FIM. After 12 weeks of full weight bearing, 51.2% of participants achieved the maximum score on the motor FIM. The correlation between the revised HiMAT and LEFS was weak ( r = 0.39; P = .012), which indicated a weak relationship between self‐reported mobility problems and actual performance. The revised HiMAT was more responsive than the motor FIM and the LEFS, based on the proportion of persons who exceeded the minimal detectable change score over a period of 6 and 12 weeks. Conclusion: The revised HiMAT is more responsive to change than the LEFS and motor FIM, and less susceptible to a ceiling effect than the motor FIM for persons with orthopedic multitrauma. It has poor‐to‐moderate concurrent validity with the LEFS and motor FIM, which suggests that it may be measuring a different aspect of mobility.